The Influence of the Ability to Recognize Opportunities on Entrepreneurial Success is Controlled by the Availability of Resources - Dhimas, Arya; Herlianti, Anggun Oktavia; Mubarok, Teten Mohammad Sapril (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
The ability to recognize opportunities is one of the key factors in entrepreneurial success. This ability encompasses other aspects that can contribute to entrepreneurial success, such as the availability of resources. The purpose of this study was to determine the influence of opportunity recognition ability on entrepreneurial success, moderated by resource availability, among small and medium-sized enterprises (SMEs) of retail or traditional merchants in Leles District, Garut Regency. This research employed a quantitative correlational and causal method to examine the relationship between two variables mediated by another variable. The sample consisted of SMEs of retail or traditional merchants in Leles District, Garut Regency. Data was collected using a questionnaire adapted and modified from Karuhanga (2022) and Chang & Chen (2020). The results showed that there is a significant influence of Opportunity Recognition Ability on Entrepreneurial Success. However, Resource Availability was not proven to moderate this relationship. The overall research model in explaining Entrepreneurial Success indicated relatively weak influence. Recommendations are provided for future research, including exploration on a larger business scale.